Mothers of the Municipality : Women, Work, and Social Policy in Post-1945 Halifax. - Fingard, Judith (University of Toronto Press, 2004)
Mothers of the Municipality explores women's activism and the provision of services at the community level. If the adage ""think globally; act locally"" has any application in modern history, it is with the women who fought many of the battles in the larger war for social justice.